The Foreign Graduates Education Policy of Beasiswa NTB: The Public Perspectives - Mahurni, Mahurni (Angstrom Centre of Education, 2025)
The majority of scholarship providers in Indonesia typically mandate that scholarship recipients must return to their home country upon the completion of their studies. However, the Beasiswa NTB, a scholarship programme sponsored by the regional government of NTB, stands as an exception to this requirement, allowing recipients to study abroad without the obligation of returning home. The government of NTB permits recipients of awards to pursue professional opportunities either domestically or internationally. The policy document lacks comprehensive clauses pertaining to this policy, resulting in minimal concern from both the general public and academic community. The objective of this study is to examine the public perceptions regarding this particular policy. This study employs a qualitative research approach, involving a sample of 128 participants from various demographic backgrounds. The data collection method utilised open-ended questionnaires to gather responses from the respondents. The research findings offer valuable insights to local governments and relevant stakeholders, highlighting the necessity of reviewing and reissuing policies to effectively address regional needs and ensure reciprocal local spending.